2021
DOI: 10.52162/3.2021111
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Students in Using Online Learning Platform During the Covid-19 Lockdown in Indonesia

Abstract: This study explores students’ experience using online learning during the COVID 19 in Indonesia. The study employed qualitative data from an online questionnaire and interview through WhatsApp voice call. The experience of the five students during their learning online was examined, analyzed, and described. The findings showed that the five students revealed cognitive and affective responses. There were general themes presented in their responses, including (a) Prefer to study in a real classroom, (b) Creative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…"Of course, I prefer offline learning because we can meet friends, can interact physically face to face and chat with each other and can also receive material to the fullest by the teachers who usually teach us at school". Novita et al, in their research finding, reveal the same fact that the students favor learning in a regular educational setting [31].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…"Of course, I prefer offline learning because we can meet friends, can interact physically face to face and chat with each other and can also receive material to the fullest by the teachers who usually teach us at school". Novita et al, in their research finding, reveal the same fact that the students favor learning in a regular educational setting [31].…”
Section: Resultsmentioning
confidence: 87%
“…Online learning makes both teachers and students have a hard time. However, many students also enjoy receiving online learning [19][20][21]. The latest study found that the majority of students strongly agreed that high-tech gadgets are pricey, which may be a sign that there is a financial issue prohibiting the students from having access to the necessary resources for online learning.…”
Section: Introductionmentioning
confidence: 99%